Different Intensities of Treadmill Running Exercise do Not Alter Melatonin Levels in Rats - Siqueira, Ionara Rodrigues; Moysés, Felipe dos Santos; Elsner, Viviane; Farias, Cristiane; Medeiros, Liciane; Torres, Iraci Lucena da Silva (Clinical and Biomedical Research, 2011)
Background: Regular and moderate exercise has been considered an interesting neuroprotective strategy. Our research group demonstrated that a protocol of moderate exercise on a treadmill reduced, while a protocol of high-intensity exercise increased in vitro ischemic cell damage in Wistar rats. The molecular mechanisms by which physical exercise exerts neuroprotective effects remain unclear. Accumulating evidence suggests that exercise may have short- and long-term effects on melatonin secretion in humans. Melatonin, the main product of the pineal gland, has been shown to have neuroprotective effects in models of brain and spinal cord injury and cerebral ischemia. A dual modulation of melatonin secretion by physical activity has also been demonstrated. This study aimed to investigate the effect of different exercise intensities, moderate- and high-intensity exercise, on serum melatonin levels in rats. Methods: Thirty-five adult male Wistar rats were divided into non-exercised (sedentary) and exercised (20- or 60-min sessions) groups. The exercise protocols consisted of two weeks of daily treadmill training. Blood samples were collected approximately 16 hours after the last training session (8:00-10:00) and melatonin levels were assayed by ELISA. Results: The exercise protocols, two weeks of 20 min/day or 60 min/day of treadmill running, did not affect serum melatonin levels. Conclusion: Our data demonstrated that melatonin levels may not be directly involved in the exercise-induced, intensity-dependent dual effect on in vitro ischemia.